2009
DOI: 10.1007/s11705-009-0253-y
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer-stabilized emulsions on the basis of interactions between β-lactoglobulin and ι-carrageenan

Abstract: ι-Carrageenan and β-lactoglobulin (β-lg) stabilized oil-in-water (O/W) emulsions, which can be used for the oral administration of bioactive but environmentally sensitive ingredients, have been successfully prepared. The effects of protein/polysaccharide ratios, total biopolymer concentration, environmental stress (thermal processing and sonication), and pH on the complex formation between ι-carrageenan and β-lactoglobulin have been investigated. We found that β-lactoglobulin and ι-carrageenan stabilized emuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It was found that whey proteins have a better emulsifying capacity than traditional emulsifiers and that β-lactoglobulin-stabilized emulsions showed higher resistance to gravitational separation (11). The isoelectric point (pI) of whey proteins was reported as pI≈5.2 (10,12). At pH values higher than the pI (e.g., pH 6), the whey proteins have a negative charge, whereas at pH values below the pI (e.g., pH 4), they are positively charged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that whey proteins have a better emulsifying capacity than traditional emulsifiers and that β-lactoglobulin-stabilized emulsions showed higher resistance to gravitational separation (11). The isoelectric point (pI) of whey proteins was reported as pI≈5.2 (10,12). At pH values higher than the pI (e.g., pH 6), the whey proteins have a negative charge, whereas at pH values below the pI (e.g., pH 4), they are positively charged.…”
Section: Introductionmentioning
confidence: 99%
“…1) is an anionic polysaccharide with a pK a value of ≈2 (8) and would be negatively charged at all pH values used throughout this study (pH>2). A study by Ru et al (12) indicated that stable emulsions could be obtained with a combination of β-lactoglobulin and ι-carrageenan at pH values of 3.4 and 4, depending on the protein/polysaccharide ratio used. Contrary, it was found that extensive flocculation occurred at pH 6.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, renewably sourced biopolymers have garnered significant investigation into their ability to stabilize emulsions. These polymers have the advantage of being hypoallergenic, biocompatible, and biodegradable [ 10 , 11 , 12 , 13 ]. By evaporating the aqueous phase from mainly o/w emulsions using spray-drying or freeze-drying, dry emulsions could be produced from biopolymer dispersions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heating the whey proteins above 80 °C denatures the proteins, leading to a very viscous aqueous dispersion once dissolved. The high viscosity of the dispersion improves the stability of the resultant emulsions and may find higher-value utilization, such as in drug delivery systems [ 13 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these emulsion-based delivery systems could release in response to a specific pH trigger similar to human digestive system. In our previous paper, we found the optimum concentrations of β-lactoglobulin and ι-carrageenan for the formation of stable oil-in-water (O/W) emulsions at pH values of both 4.0 and 3.4 were 0.3-0.6 and 0.4-0.7 wt %, respectively (13). High-pressure homogenization has been routinely used to engineer nano-or submicrometer nutraceutical dispersions (14).…”
Section: Introductionmentioning
confidence: 99%